ANALISIS PENGARUH CAR, DANA PIHAK KETIGA (DPK), NPL, dan LDR TERHADAP PROFITABILITAS PERBANKAN DENGAN LDR SEBAGAI VARIABEL INTERVENING - Wityasari, Meryta; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2014)
The aim of this research is to identify and analyze the determinants of return on Assets (ROA) in General Banking of Indonesia in the period of 2009 – 2013. ROA is dependent variable in this research, as profitability indicator. There are three independent variables that used, which are Capital Adequacy Ratio (CAR), Third Party Funds (TPF), Non Performing Loan (one year before) (NPLt-1), and an intervening variable which is Loan to Deposit Ratio (LDR). Sampling technique used is purposive sampling with criteria as General Banking in Indonesia who provide annual reports and traded on Indonesia Stock Exchange (IDX) during period 2009 through 2013 and forwarded to Bank Indonesia. Obtained by amount sampel as much 22 companies from 36 banking company in Indonesia 2009-2013 period. Analyzed with Path Analysis technique. The data is analyzed using AMOS 21 program.The result of this study proving that NPLt-1 and LDR have positive relationship and statistically significant. The CAR and TPF have positive and significant relationship toward ROA. NPLt-1 has negative relationship and significant toward ROA. Then, there isn’t variable which has significant relationship toward ROA mediated by LDR as intervening variable.